2021
DOI: 10.3390/jof7121053
|View full text |Cite
|
Sign up to set email alerts
|

Host-Induced Gene Silencing of a G Protein α Subunit Gene CsGpa1 Involved in Pathogen Appressoria Formation and Virulence Improves Tobacco Resistance to Ciboria shiraiana

Abstract: Hypertrophy sorosis scleroteniosis caused by Ciboria shiraiana is the most devastating disease of mulberry fruit. However, few mulberry lines show any resistance to C. shiraiana. An increasing amount of research has shown that host-induced gene silencing (HIGS) is an effective strategy for enhancing plant tolerance to pathogens by silencing genes required for their pathogenicity. In this study, two G protein α subunit genes, CsGPA1 and CsGPA2, were identified from C. shiraiana. Silencing CsGPA1 and CsGPA2 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…CsGPA1, a G protein α subunit gene, was identified and characterized by its roles in Ciboria shiraiana. The CsGPA1-silenced strains were significantly reduced in appressoria formation compared to the wild-type and empty vector strains [109].…”
Section: Other Fungimentioning
confidence: 87%
“…CsGPA1, a G protein α subunit gene, was identified and characterized by its roles in Ciboria shiraiana. The CsGPA1-silenced strains were significantly reduced in appressoria formation compared to the wild-type and empty vector strains [109].…”
Section: Other Fungimentioning
confidence: 87%
“…Previous studies have shown that Gα subunits regulate the growth and development of fungal species [ 33 ]. The silence of two Gα subunit genes in Ciboria shiraiana , CsGPA1 and CsGPA2 , had no effect on mycelial growth, but they reduced the number of sclerotia and increased the weight of a single sclerotia [ 34 ]. In Aspergillus fumigatus , deletion of gpaB and ganA decreased colony growth, while growth was heightened in a gpaA deletion strain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The silencing of CsGPA2 , the Gα subunit gene of C. shiraiana , resulted in a slight increase in peroxidase and laccase activities. However, the virulence of CsGPA1 silencing strain was reduced, but peroxidase and laccase activities were normal [ 34 ]. In this study, both overexpression and interfering strains significantly enhanced laccase activity compared to WT ( Figure 2 C).…”
Section: Discussionmentioning
confidence: 99%
“…Host-induced gene silencing (HIGS) enhances sclerotiorum, but it did decrease the quantity of sclerotia and increase the weight of individual sclerotia. Interestingly, only the strain with CsGPA1-silenced exhibited reduced virulence (Zhu et al 2021). Additionally, a study showed a positive correlation between sclerotinia virulence and colony diameter, but no correlation was found between virulence and the number, size, or weight of sclerotia.…”
Section: Possible Inhibitory Evidence Regarding the Two Acids On S Sc...mentioning
confidence: 98%